Chiral Phosphoric Acid‐Catalyzed Enantioselective Formal [4+2] Cycloaddition Between Dienecarbamates and 2‐Benzothioazolimines. Issue 10 (25th April 2022) - Ma, Wei‐Yang; Montinho‐Inacio, Emeric; Iorga, Bogdan I.; Retailleau, Pascal; Moreau, Xavier; Neuville, Luc; Masson, Géraldine
Abstract: An enantioselective chiral phosphoric acid catalyzed formal [4+2] cycloaddition between 2‐benzothiazolimines and N ‐H‐1, 3‐dienecarbamates is described. A divergence in reaction pathways was observed depending on the dienes employed. The reaction performed with 4‐substituted dienes produced benzothiazolopyrimidines as major product in yields ranging from 42 to 67%, as single diastereoisomer and with enantioselectivity between 93 and 99%. The same reaction performed with 3‐substituted dienes, however, gave highly enantioenriched 1, 2, 3, 4‐tetrahydroquinolines as the major products albeit with moderate diastereoselectivity. Abstract :